Clear Cell Carcinoma of Ovary: A Rare Case Report - Rajput, Kirti; Maheshwari, Veena; Ahmed, Murad; Usman, Syeda Iqra; Sahu, Shushant (Annals of Pathology and Laboratory Medicine, 2023)
Abstract Ovarian cancer is a heterogeneous disease and is morphologically divided into six types of epithelial ovarian tumors -serous, mucinous, endometrioid, brenner, clear cell and undifferentiated carcinoma. Clear cell carcinoma (CCC) represents 2-10% of all epithelial ovarian cancers. The median age of presentation is between 40 to 70 years with peak incidence at 52 yrs. We present a case of 25-year unmarried female who presented with complaints of polymenorrhagia and abdominal distension for past 3 months. Ultrasound of abdomen revealed complex mass with solid component seen in the left adnexal region measuring 15x12x10 cm. CT scan showed left sided adnexal cystic mass with solid mural component with thick internal septation. Imprint smear from Left ovary, showed singly scattered and clusters of cells with round to oval vesicular nuclei and scant amount of eosinophilic cytoplasm. Background showed cystic macrophages, mixed inflammatory infiltrate and hemorrhage, suggestive of a serous tumour. On gross examination, of left ovary a globular solid cystic mass measuring 15x12x6 cm was received. On microscopic examination, tumor cells were arranged in small sheets, glands and tubules separated by fibrous stroma. These were lined by clear and hobnail cells. The cells were cuboidal to columnar with abundant clear cytoplasm and eccentric nucleus. Immunohistochemistry showed EMA and PanCK positivity. Overall morphology and IHC favored a diagnosis of Clear cell carcinoma of left ovary. The tumor was graded as pT2bN0Mx. The patient was followed up postoperatively. CA-125 returned to normal levels during follow-up.